2016
DOI: 10.1002/hed.24584
|View full text |Cite
|
Sign up to set email alerts
|

Amplification and protein overexpression of cyclin D1: Predictor of occult nodal metastasis in early oral cancer

Abstract: Cyclin D1 is a predictive biomarker for occult nodal metastases in early FOM cancers. Prospective research on biopsy material should confirm these results before implementing its use in routine clinical practice. © 2016 Wiley Periodicals, Inc. Head Neck 39: 326-333, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…After elimination of duplicate records, the title and abstract of 133 potentially eligible studies were screened, leading to the selection of 52 studies for evaluation of their full text. Among these articles, 18 met all eligibility criteria for inclusion in the qualitative study and quantitative meta‐analysis …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After elimination of duplicate records, the title and abstract of 133 potentially eligible studies were screened, leading to the selection of 52 studies for evaluation of their full text. Among these articles, 18 met all eligibility criteria for inclusion in the qualitative study and quantitative meta‐analysis …”
Section: Resultsmentioning
confidence: 99%
“…Among these articles, 18 met all eligibility criteria for inclusion in the qualitative study and quantitative meta-analysis. [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] Table 1 summarizes the characteristics of the 18 selected studies, which include 1633 patients with HNSCC. The sample size of these studies ranges between 13 and 222 patients.…”
Section: Results Of the Search Of The Literaturementioning
confidence: 99%
“…Furthermore, cyclin D1 targeted to the mammary gland was sufficient for the induction of mammary tumorigenesis 10,11 . Clinical studies have shown a correlation between cyclin D1 expression and tumorigenesis and increased cyclin D1 expression is associated with tumor invasion and metastasis [12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Cyclin D1 overexpression has been related with amplification of the CCND1 gene in several tumours including OSCC [ 22 , 27 , 28 ]. The activation of the pathways involved in cyclin D1 expression appears to be essential in the development of human cancers, including oral cancer [ 27 ].…”
Section: Discussionmentioning
confidence: 99%